Reflections on My Training Experiences: University of Oxford, UK / Dr Shubashini Gnanasan - Gnanasan, Shubashini (Faculty of Pharmacy, 2023)
Being a research fellow at the University of Oxford under the guidance of Professor Masliza Mahmod has been a rewarding experience for me. It is certainly a privilege to be part of the clinical trial team at the Oxford Centre for Clinical Magnetic Resonance Research (OCMR), Division of Cardiovascular Medicine, John Radcliffe Hospital. I am currently involved in setting up and running an open label trial to collect long term safety and tolerability data for Aficamten in patients with hypertrophic cardiomyopathy (HCM). I have also had the opportunity to collaborate with other researchers and observe other trials that are being conducted in patients with HCM. So far, I have participated in research meetings and observed clinicians performing echocardiography, cardiac spectroscopy, cardiac magnetic resonance imaging and cardiac pulmonary exercise test. These observations allowed me to understand the work of the clinicians and the time taken to conduct these tests. I also accompany the research nurses and physicians during trial visits and they had been very kind in explaining their roles. I also accompany the clinical trial pharmacist during trial visits. In order to participate in research activities in OCMR, I had to complete several research trainings which has certainly enhanced my understanding of the subject matter and the research ecosystem. Being practically immersed in the trial unit on a daily basis has allowed me to observe the dedication of the clinical trial team and the efforts taken to make sure the trials run smoothly.